Potential in-class strategies to increase children’s vegetable consumption - Sharp, Gemma; Pettigrew, Simone; Wright, S.; Pratt, Steve; Blane, S.; Biagioni, Nicole (Cambridge University Press, 2017)
Objective: The Crunch&Sip programme is a school-based nutrition initiative designed to increase the fruit, vegetable and water intakes of primary-school children. In recognition of the notable deficits in children’s vegetable consumption, the present study explored the receptivity of school staff to a realignment of the Crunch&Sip programme to feature a primary focus on vegetable consumption. This involved investigating school staff members’ perceptions of relevant barriers, motivators and facilitators. Design: A multi-method approach was adopted that involved four focus groups and a survey (administered in paper and online formats) containing a mixture of open- and closed-ended items. Setting: Western Australia. Subjects: Staff from Western Australian schools participated in the focus groups (n 37) and survey (n 620). Results: School staff were strongly supportive of modifying the Crunch&Sip programme to focus primarily on children’s vegetable consumption and this was generally considered to be a feasible change to implement. Possible barriers identified included children’s taste preferences and a perceived lack of parental support. Suggested strategies to overcome these barriers were education sessions for parents and children, teachers modelling vegetable consumption for their students and integrating vegetable-related topics into the school curriculum. Conclusions: School staff are likely to support the introduction of school-based nutrition programmes that specifically encourage the consumption of vegetables. Potential barriers may be overcome through strategies to engage parents and children.